Program Implementation Merdeka Belajar Kampus Merdeka Through The Implementation of IKU I PTN Standards of The Ministry of Education and Culture (Case Study at University of Indonesia) - Arief Sukma Yulianto; Vishnu Juwono (Asian Journal of Social and Humanities, 2024)
Education is an important element in the development of human civilization from time to time to be able to make adjustments to all needs both situational and dispositional. The rapid development in aspects of science and technology requires all of us to go towards changes that also run rapidly in various aspects of life. The demands for these changes include the way of mindset, outlook on something new, social, economic and cultural changes that simultaneously occur significantly, related to these dynamics, universities must provide a quick response in responding to all challenges which of course must be done appropriately, and based on Based on Evidence. The Minister of Education and Culture of the Republic of Indonesia under the leadership of Nadiem Makarim issued a new policy, namely the Independent Learning Program – Independent Campus (MBKM), in this policy there are four core policies that will be targeted from this program, namely, granting autonomous authority to universities related to the addition of new study programs, automatic reaccreditation process, facilitating procedures for changing the status of universities from universities The Public Service Agency (PTNBLU) became a Legal Entity State University (PTNBH), and the latter gave freedom to its students to study outside their study program and even outside their campus. The four programs are basically intended to provide universities with ease to be more independent, autonomous, less bureaucratic, and innovative.